The impact of inflammation and acute phase activation in cancer cachexia - Robinson, Tyler P.; Hamidi, Tewfik; Counts, Brittany; Guttridge, Denis C.; Ostrowski, Michael C.; Zimmers, Teresa A.; Koniaris, Leonidas G. (Frontiers in Immunology, 2023)
The development of cachexia in the setting of cancer or other chronic diseases is a significant detriment for patients. Cachexia is associated with a decreased ability to tolerate therapies, reduction in ambulation, reduced quality of life, and increased mortality. Cachexia appears intricately linked to the activation of the acute phase response and is a drain on metabolic resources. Work has begun to focus on the important inflammatory factors associated with the acute phase response and their role in the immune activation of cachexia. Furthermore, data supporting the liver, lung, skeletal muscle, and tumor as all playing a role in activation of the acute phase are emerging. Although the acute phase is increasingly being recognized as being involved in cachexia, work in understanding underlying mechanisms of cachexia associated with the acute phase response remains an active area of investigation and still lack a holistic understanding and a clear causal link. Studies to date are largely correlative in nature, nonetheless suggesting the possibility for a role for various acute phase reactants. Herein, we examine the current literature regarding the acute phase response proteins, the evidence these proteins play in the promotion and exacerbation of cachexia, and current evidence of a therapeutic potential for patients.